The Phytotoxicity of Meta-Tyrosine Is Associated With Altered Phenylalanine Metabolism and Misincorporation of This Non-Proteinogenic Phe-Analog to the Plant's Proteome - Zer, Hagit; Mizrahi, Hila; Malchenko, Nikol; Avin-Wittenberg, Tamar; Klipcan, Liron; Ostersetzer-Biran, Oren (Frontiers in Plant Science, 2020)
Plants produce a myriad of specialized (secondary) metabolites that are highly diverse chemically, and exhibit distinct biological functions. Here, we focus on meta-tyrosine (m-tyrosine), a non-proteinogenic byproduct that is often formed by a direct oxidation of phenylalanine (Phe). Some plant species (e.g., Euphorbia myrsinites and Festuca rubra) produce and accumulate high levels of m- tyrosine in their root-tips via enzymatic pathways. Upon its release to soil, the Phe-analog, m-tyrosine, affects early post-germination development (i.e., altered root development, cotyledon or leaf chlorosis, and retarded growth) of nearby plant life. However, the molecular basis of m-tyrosine-mediated (phyto)toxicity remains, to date, insufficiently understood and are still awaiting their functional characterization. It is anticipated that upon its uptake, m-tyrosine impairs key metabolic processes, or affects essential cellular activities in the plant. Here, we provide evidences that the phytotoxic effects of m-tyrosine involve two distinct molecular pathways. These include reduced steady state levels of several amino acids, and in particularly altered biosynthesis of the phenylalanine (Phe), an essential α-amino acid, which is also required for the folding and activities of proteins. In addition, proteomic studies indicate that m-tyrosine is misincorporated in place of Phe, mainly into the plant organellar proteomes. These data are supported by analyses of adt mutants, which are affected in Phe-metabolism, as well as of var2 mutants, which lack FtsH2, a major component of the chloroplast FtsH proteolytic machinery, which show higher sensitivity to m-tyrosine. Plants treated with m-tyrosine show organellar biogenesis defects, reduced respiration and photosynthetic activities and growth and developmental defect phenotypes.